Attention to social stimuli is modulated by sex and exposure time in tufted capuchin monkeys - Schino, Gabriele; Carducci, Paola; Truppa, Valentina (Animal behaviour, 2020)
The dot probe task is an experimental procedure commonly used to study how animals (including humans) pay attention to different stimuli. In this study, we evaluated how different durations of image exposure modulate the response to this task and how male and female tufted capuchin monkeys (Sapajus spp.) respond to a dot probe presented immediately after different social stimuli. Subjects were shown pairs of images of unfamiliar conspecifics: a male versus a female or two individuals grooming versus two individuals not engaged in grooming (nongrooming). With shorter image exposures (250ms) both sexes showed shorter response times to the dot probe after presentation of (i.e. biased their attention towards) images of unfamiliar males compared to females, and did not show any bias towards images of grooming compared to nongrooming. With longer image exposures (1000ms) females biased their attention towards images of unfamiliar females, while males did not show any difference; in contrast, males biased their attention towards images of grooming compared to nongrooming, while females did not show any difference. We interpret these results as showing that responses to the dot probe task with different image exposures reflect different attentional phenomena, and that the two sexes differ in how social stimuli affect their attention. •We assessed attention to social stimuli in capuchin monkeys using a dot probe task.•Stimuli were images of unfamiliar conspecifics shown for 250 or 1000ms.•Both sexes biased their attention towards images of males shown for 250ms.•Females biased their attention towards images of females shown for 1000ms.•Males biased their attention towards images of grooming shown for 1000ms.